Influence of psychosocial safety climate on occupational health and safety: a scoping review - Mustapha Amoadu; Edward Wilson Ansah; Jacob Owusu Sarfo (BMC, 2023)
Abstract Background Creating a healthy, decent and safe workplace and designing quality jobs are ways to eliminate precarious work in organisations and industries. This review aimed at mapping evidence on how psychosocial safety climate (PSC) influence health, safety and performance of workers. Methods A literature search was conducted in four main databases (PubMed, Scopus, Central and Web of Science) and other online sources like Google Scholar. A reference list of eligible studies was also checked for additional papers. Only full-text peer-reviewed papers published in English were eligible for this review. Results A search in the databases produced 13,711 records, and through a rigorous screening process, 93 papers were included in this review. PSC is found to directly affect job demands, job insecurity, effort-reward imbalance, work-family conflict, job resources, job control and quality leadership. Moreover, PSC directly affects social relations at work, including workplace abuse, violence, discrimination and harassment. Again, PSC has a direct effect on health, safety and performance outcomes because it moderates the impact of excessive job demands on workers' health and safety. Finally, PSC boosts job resources' effect on improving workers' well-being, safety and performance. Conclusion Managers' efforts directed towards designing quality jobs, prioritising the well-being of workers, and fostering a bottom-up communication through robust organisational policies, practices, and procedures may help create a high organisational PSC that, in turn, promotes a healthy and decent work environment.